Study the Nature and the Effects of the Impurities of Phosphate Rock in the Plants of Production of Phosphoric Acid - Chaabouni, Ahmed; Chtara, Chaker; Nzihou, Ange; Feki, Hafed EL (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
Phosphate rocks from different deposits vary widely in composition, and these variations have important effects in phosphoric acid production. All phosphate rocks contain many impurities. Knowledge of the nature and contents of the various elements in the phosphate is required in the manufacturing process of phosphoric acid. All these chemical characteristics can help the operator to foresee its objectives under the operating conditions and the cost of production in the manufacturing process of phosphoric acid. Two Tunisian natural phosphates coming from two different deposits were selected. We propose in this work studying the effects of the impurities that depending on their concentration can affect decisively the behavior of these ores in the process of production of phosphoric acid. Study the chemical composition of these ores is carried out according to standard analytical methods used for raw phosphates. The results obtained show a slight difference in chemical properties between the two types of sedimentary phosphates and their aptitude to be used in the plants of production of phosphoric acid.Â 